MiR‐506‐3p alleviates uncontrolled osteoclastogenesis via repression of RANKL/NFATc1 signaling pathway. Issue 12 (5th May 2020) - Dinesh, Palani; Kalaiselvan, Sowmiya; Sujitha, Sali; Rasool, Mahaboobkhan
Abstract: Bone erosion is the major cause of deformities in autoimmune disease conditions such as osteoporosis and rheumatoid arthritis. Aberrant receptor activator of nuclear factor kappa B ligand (RANKL) secretion in bone disorders have been implicated to promote uncontrolled osteoclast differentiation through the regulation of nuclear factor of activated T cells 1 (NFATc1) transcription factor. This phenomenon is governed by several molecular factors including microRNAs, which are under‐expressed during disease progression. This report focuses on elucidating the molecular mechanism of miR‐506‐3p towards the RANKL/NFATc1 pathway. miR‐506‐3p showed high binding affinity towards NFATc1 (ΔG = −22.4 kcal/mol). Bone marrow‐derived macrophages (BMMs) isolated from rats stimulated with RANKL (100 ng/ml) showed active expression of NFATc1 which differentiated into mature osteoclasts. Moreover, NFATc1 activation resulted in downstream secretion of various bone resorptive enzymes (cathepsin K, carbonic anhydrase II, tartarate acid phosphatase, and matrix metalloproteinase 9) which lead to active bone resorption. However, transfection of miR‐506‐3p resulted in selective repression of NFATc1 inside the cells. This further resulted in the diminished release of bone resorptive enzymes that were essential for the degradation of the bone. Overall, we predict that miR‐506‐3p can be used as a molecular intervention for RANKL/NFATc1 mediated osteoclastogenesis. Abstract : Overall inhibitory effect of miR‐506‐3p towards receptor activator of nuclear factor kappa B ligand/nuclear factor of activated T cells 1 signaling in bone marrow‐derived macrophages.